Design and Development Of A 6-DOF System For Virtual Bicycle Simulator - Hwa, Jen Yap (Kementerian Pendidikan Tinggi (KPT), Malaysia, 2018)
Link to publisher's homepage at http://www.mohejournal.com/index.php/mohe